Uncrewed operational medical support: a doctrinal gap in UK and NATO military medicine - Owen David Williams; Ed Barnard (BMJ Military Health, 2026)
Uncrewed (Ux) systems are now central to contemporary military operations, providing reconnaissance, precision strike, logistics and persistence in environments where crewed platforms may be exposed, unavailable or unacceptable. Their use for the evacuation of operational casualties is therefore an intuitive extension of current capability, particularly in dispersed, contested and casualty-dense settings. This analysis examines current UK and NATO doctrine and future concepts relating to uncrewed air, ground and maritime systems with specific attention to their potential role in casualty evacuation. Across the UK and NATO publications, uncrewed systems are consistently presented as important to future force design, multi-domain integration and operational resilience. However, there is little practical doctrinal guidance on their use for casualty movement, and almost no detail on clinical governance, command responsibility, monitoring, escort, acceptability or the boundary between casualty evacuation and medical evacuation. The most mature doctrinal material concerns uncrewed aerial systems; ground and maritime applications are less developed and medical applications remain largely conceptual. We argue that uncrewed systems should initially be considered for medical logistics and selected casualty evacuation tasks rather than assumed to provide medical evacuation in the conventional sense. A staged model is proposed, progressing from uncrewed resupply and CASEVAC through remotely monitored evacuation towards an integrated cross-domain uncrewed medical care capability. Before operational adoption, UK Defence Medical Services should lead development and testing of clinical tactics, techniques and procedures, standard operating procedures and assurance mechanisms.